James Brown papers - Brown, James, 1766-1835.
Volumes containing correspondence and legal and commercial documents pertaining to Brown's Louisiana law practice and his service as U.S. senator. Papers primarily concern legal practices and social conditions in Louisiana. Includes papers relating to the court-martial of U.S. Army officer, Thomas Butler (1804-1805). Correspondents include James's brother, U.S. Senator John Brown, and a second brother, Samuel.
U.S. senator, diplomat, and lawyer.
Collection material in English, with Spanish.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brown, John, -- 1757-1837 -- Correspondence; Brown, Samuel, -- 1769-1837 -- Correspondence; Butler, Thomas, -- 1748-1805.; United States. -- Army -- Officers; United States. -- Congress. -- Senate; Courts-martial and courts of inquiry; Procedure (Law) -- Louisiana; Louisiana -- Politics and government; Louisiana -- Social conditions; Diplomats; Lawyers; Senators, U.S.